Stimulation of photosynthetic characteristics of Ginkgo biloba L. during leaf growth - Yang, Xian-Song; Chen, Guo-Xiang (Bangladesh Journal of Botany, 2014)
Photosynthetic pigments, biochemical activities and chlorophyll a fluorescence kinetics were investigated to survey the photosynthetic characteristics of Ginkgo biloba L. during leaf growth. The content of total chlorophyll increased rapidly while the content of carotenoids changed a little. The content of ATP, the activity of O2 evolution of chloroplasts, the electron transport activities, the activity of photophosphorylation and the activities of Ca2+ - and Mg2+ - ATPase were strengthened. All leaves at various growing stages exhibited typical chlorophyll ? fluorescence transient, the intensity of fluorescence in the chlorophyll ? fluorescence transient (OJIP) increased during leaf growth. Photosynthetic abilities gradually increased as the leaves grew. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19749 Bangladesh J. Bot. 43(1): 73-77, 2014 (June)